Childfree in The Perspective of Hadiths Ahkam: Thematic Study of Hadith on 'Azal with a Maqāṣid al-Sharī'ah Approach - Nadhiran, Hedhri; Mirzan, Muhammad; Mardiah, Anisatul; Ilyas, Deddy; Nugroho, Nugroho (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2026)
Childless marriage, or an agreement between a husband and wife not to have children after marriage, is currently a trending topic on various social media platforms. Based on this issue, the formulation of this research is how childless marriages are seen from the hadith perspective and what solutions the hadiths offer to overcome this problem. The research method used is a literature study using the theory of hadith hermeneutics. This research was carried out by collecting and analyzing various written sources, such as books, journals and articles as well as Mu'tabar hadith books. The results of the study indicate that the hadiths regarding the permissibility of 'azal studied are of authentic quality and can be accepted as evidence in religion. Regarding understanding, thematic studies, especially from the historical aspects, show that the desire to perform 'azal expressed by a companion to the Prophet Muhammad was related to the condition of his wife who was breastfeeding, so the use of these hadiths as a basis for the permissibility of childfree needs to be reviewed. This shows a significant difference between childfree and the permissibility of 'azal. That the permissibility of 'azal does not mean an attitude or desire to not have children permanently, However, it is only conditional and temporary. This differs from childfree, which actually refuses to have children in a marriage. Meanwhile, a thematic analysis involving other